Glycyrrhizin Attenuates Mucus Production by Inhibition of MUC5AC mRNA Expression In Vivo and In Vitro - Yuki Nishimoto; Akinori Hisatsune; Hiroshi Katsuki; Takeshi Miyata; Kazumi Yokomizo; Yoichiro Isohama (Elsevier, 2010)
We have previously indicated that glycyrrhizin (GL), a major component of licorice, has glucocorticoid-like anti-inflammatory effects in cultured airway epithelial cells and suggested its usefulness in the treatment of inflammatory respiratory diseases. On the other hand, mucus hypersecretion in the respiratory tract and goblet cell hyperplasia in the airway epithelium contribute to the morbidity and mortality associated with airway inflammatory diseases. This study, therefore, aimed to examine the effects of GL on airway mucus hyperproduction and define the mechanisms behind these effects. In an in vivo model, GL significantly attenuated goblet cell hyperplasia and MUC5AC mRNA expression in mice treated with lipopolysaccharide or interleukin-4. In addition, GL significantly attenuated MUC5AC protein and mRNA expression by tumor growth factor (TGF)-α in cultured NCI-H292 cells. GL also attenuated TGF-α-stimulated MUC5AC promoter activity in a luciferase reporter gene assay, but did not affect the stability of MUC5AC mRNA. Taken together, we concluded that GL has an inhibitory effect on mucus hyperproduction both in vivo and in vitro and that GL-mediated inhibition may be mediated through the inhibition of MUC5AC gene transcription.[Supplementary Figures: available only at http://dx.doi.org/10.1254/jphs.09344FP] Keywords:: glycyrrhizin, mucin, goblet cell, airway inflammation, MUC5AC